Molecular dynamics study of aqueous uranyl in hydrophilic mesoporous confinement: the case of slit-like pore in amorphous silica - Patsahan, T.; Holovko, M. (Condensed Matter Physics, 2007)
Molecular dynamics simulations are used to study structural and dynamic properties of water and aqueous uranyl ion adsorbed in a slit-like pore of amorphous silica. Calculations are performed for the flexible SPC/E water model in the atomistically detailed pores with sizes in the range of 2.0–5.0 nm. The hydroxyl groups on the pore surfaces lead to a strong adsorption and strongly affect the mobility of water molecules. The uranyl ion and its aqueous environment adsorbed in the pores are studied at the room temperature for different amounts of water. The effect of hydroxylated silica pores on the formation of uranyl hydrate complexes is discussed within the present study.